Mesoporous Materials Properties and Applications - Krishnappa, Manjunath (IntechOpen, 2019)
The basic theme of this book is to understand the fundamentals and importance of porous functional materials, their properties, and significant applications like solar cells, batteries, photovoltaics, energy conversions, and mesoporous materials. This book covers the fundamentals of mesoporous materials, and various methods of synthesis, properties, and applications in different sectors.